Challenges faced by local building construction projects in implementing and achieving ISO 9000 requirements - Chew, Keng Chiak. (2009)
This dissertation explores the challenges and problems faced by typical local building construction projects of local medium size construction companies (G7 to G8) in implementing and achieving ISO 9000 requirements. The main contractors for the projects surveyed are Chinese family owned private companies. Survey results reflect the situation of the typical local main contractor and not the better established government linked companies (GLC) and foreign Multi-National Corporations MNC. However, some of the challenges are common to both local and MNC.